Environmental Performance of ASEAN Countries: A Data Envelopment Analysis Approach - Rossazana, Ab. Rahim (Institute of Public Enterprise, 2015)
As far as this study is concerned, there are no existing studies which had measured the aggregate index of ASEAN environmental performance. The assessment of environmental performance is important as it provides sound information to the policy makers to improve the design of their environmental policies at upholding long-term sustainability of a nation. Employing data envelopment analysis (DEA) method, the results of this study reveal that smaller economies such as Laos, Cambodia and Brunei are found to be environmentally efficient. With respect to economic efficiency, larger economies such as Malaysia, Indonesia, the Philippines and Singapore are found to be more efficient than the smaller countries (except Brunei).